Culture Development Planning in the Special Region of Yogyakarta (Management Planning of Cultural Heritage in Kotagede District based on Community Empowerment Conservation Model) - Suryanti, Eko; Sumartono, Sumartono; Hermawan, Hermawan (Journal of Indonesian Tourism and Development Studies, 2014)
The Special Region of Yogyakarta is a cultural rich city with excellent cultural resources. Yogyakarta should manage their assets with long-term planning to keep the sustainability. There is a very unique planning process due to a combination of political, technocratic, participatory, top down and bottom up approaches. This planning process is comprehensive or integrated because its involved many actor from multisectoral, multidisciplinary, multi regulatory, and multi planning documents, etc. Local wisdoms have been coloring the planning documents. This study describe and analyze the cultural development planning in Yogyakarta especially on the Management Planning in Kotagede Cultural Heritage District. We used qualitative descriptive approach methods and Miles and Huberman analysis methods. Participation of community and Non Governmental Organization (NGO) in conservation planning of cultural heritage in this area is very significant in simplify the government task because people have been more literate in planning, have database of cultural assets, and capable of making their own decisions for the future of the region. Participatory rural appraisal (PRA) dan Rapid Rural Appraisal (RRA) were integrated in the planning process of Kotagede Heritage District management, thus it becomes a model of cultural heritage with community empowerment-based conservation. Keywords: culture development planning, comprehensive planning, heritage cultural district, community empowerment-based conservation.